Chinese views of childhood - Kinney, Anne Behnke (University of Hawaii Press, 1995)
Chinese in the twentieth century, intent on modernizing their country, condemned their inherited culture in part on the grounds that it was oppressive to the young. The authors of this pioneering volume provide us with the evidence to re-examine those charges. Drawing on sources ranging from art to medical treatises, fiction, and funerary writings, they separate out the many complexities in the Chinese cultural construction of childhood and the ways it has changed over time. Listening to how Chinese talked about children--whether their own child, the abstract child in need of education or medical care, the ideal precocious child, or the fictional child--lets us assess in concrete terms the structures and values that underlay Chinese life.